Tracking source azimuth using a single vector sensor - Felisberto, P. (2010)
This paper aims at estimating the azimuth of an underwater acoustic source with a single vector sensor. A vector sensor is a device that measures the scalar acoustic pressure field and the vectorial acoustic velocity field at a single location in space. The actual sensor technology allows to build compact vector sensors, with an operational frequency response ranging from a few hertz to several tens of kilohertz, thus the same device can be used to receive shipping noise upto dolphin whistles. It is demonstrated that one can attain a reliable estimate of the azimuth of a source with a single vector sensor. The method presented is based on the inner product between the sampled acoustic field and the different particle velocity orthogonal components. The method is very simple and low computational demanding thus, well suited to be used in mobile or light platforms where space and/or computational power requirements is of concern. It is shown that the proposed method can be used either in time or in frequency domain, giving rise to easily estimating the azimuth of several sources with non-overlapping frequency bands. The data discussed herein (ship noise, communication signals, tomographic signals) were acquired during the Makai’2005 experiment using a four element vector sensor array. It is shown that the estimates obtained with a single vector sensor are comparable with those obtained with the full vector sensor array and are inline with the expected results as known from the geometry of the experiment.